Some Experimental Investigations on Gas Turbine Cooling Performed with Infrared Thermography at Federico II - T. Astarita; G. Cardone; L. de Luca; G. M. Carlomagno (International Journal of Rotating Machinery)
This paper reviews some experimental measurements of convective heat transfer coefficient distributions which are connected with the cooling of gas turbines, performed by the authors’ research group at the University of Naples Federico II with infrared thermography. Measurements concern impinging jets, cooling of rotating disks, and gas turbine blades, which are either stationary or rotating. The heated thin foil sensor, associated with the detection of surface temperature by means of infrared thermography, is exploited to accurately measure detailed convective heat transfer coefficient maps. The paper also intends to show how to correctly apply the infrared technique in a variety of gas turbines cooling problems.